Bonding behaviour between old and new foamed concrete with different substrate surface - Mohd Marwan Hafiz, Mohd Anuar (2014)
Recent years, method of concrete strengthening has been a rising issue. In structure of concrete or concrete repairing works, the most Important element is that the bonding itself. The surface preparation of concrete substrate will give differ results in term of bonding behavior. Performance of a structural system such beams and slabs are relies on behavior of the bonding between the old and new concrete. The research intended at studying the bonding strength between the old and new foamed concrete due to surface preparations. Factors such as roughness of surface, compaction, and concrete curing affect the bond. In this study, the surface of the old concrete were partially chipped using a light jackhammers and differed in terms of its numbers. The research was also to observe failure mode pattern due to different number of chippings. Samples were tested for two different methods namely Splitting Test and Slant Shear Test. The slant shear tests were conducted to investigate the bonding strength in term of shear. For slant shear test, 12 blocks sizing 100 mm x 100 mm x 400 mm were prepared. Meanwhile, the slant shear test was conducted to measure the axial tensile strength of a concrete submitted to compression along its length. For this test, 12 cube specimens ofize 150 mm x 150 mm x 150 mm were prepared. These tests were conducted on 28 days after standard air curing because at day 28 the concrete had fully achieved its true strength. Foamed concrete was used to reduce the self-weight of the structural element compared to the conventional concrete. For each testing method, three samples were prepared and differed in term of surface roughness of 0, 10, 20 and 30 number of drill holes. From the results, S30 for Splitting test and SR30 Slant shear test showed the highest in terms of bonding strength compared to lower surface roughness with values of 2.17 N/mni2 and 21.73 N/mrn2 respectively. However, all types of surface roughness are failed intermof bonding.